Design and analysis of frequency reconfigurable antenna in S-band - Maganti Apparao; Godi Karunakar (Bulletin of Electrical Engineering and Informatics, 2023)
One of the biggest challenges in modern communication systems is to provide a single antenna for multiple applications. Existing antenna systems are limited to some applications. Therefore, it is important to design a single reconfigurable antenna for multiple applications in current communication systems. To overcome this problem, a single antenna with frequency reconfiguration capability has been developed in this work. In this work, four different frequency reconfigurable antenna layouts are investigated. To provide frequency reconfigurability, the proposed antenna comprises two P-intrinsic-N (PIN) diodes placed between the microstrip line and patch. The antenna can resonate in four states and operate at three distinct frequencies without affecting the size of the antenna by toggling the 'ON' and 'OFF' modes of the PIN diodes. The antenna can operate at three different frequency ranges, depending on the switching state of the PIN diode 2.1, 2.4 and 3.0 GHz. The voltage standing wave ratio (VSWR), gain, return loss (RL) and radiation patterns of the antennas were simulated and measured. It is clear that the proposed antenna works at different operating frequencies. The gain and RL for the corresponding frequencies are significantly improved and the radiation pattern is symmetrical.